SGLT2 Inhibitors vs. Finerenone for Slowing CKD Progression in Hypertensive Diabetic Patients with Obesity: A Comparative Effectiveness Study (Journal of AI-Powered Medical Innovations (International online ISSN 3078-1930), 2024)
Chronic kidney disease continues to be a major cause of illness and death around the world, and it's particularly common in people with type 2 diabetes, high blood pressure, and obesity. When these conditions occur together, it's a very dangerous situation for the kidneys, leading to a quicker loss of kidney function, more heart problems, and generally a worse outlook for the future (Kovesdy 2022; Mallamaci and Tripepi 2024). The usual treatments, including blocking the renin-angiotensin-aldosterone system (RAAS), haven't been very successful at stopping the disease from getting worse, so we need new, more specific drug treatments (Forbes and Gallagher 2020).Recently, SGLT2 inhibitors and finerenone have been shown to protect both the kidneys and the heart. SGLT2 inhibitors work mainly by reducing how much glucose the kidneys reabsorb, correcting the communication between the tubules and glomeruli, and reducing pressure inside the glomeruli, all of which slows down the rate at which estimated glomerular filtration rate (eGFR) declines (Vallon and Verma 2021; Bailey, Day, and Bellary 2022). Finerenone, on the other hand, works by specifically blocking the mineralocorticoid receptor, and in doing so, reduces inflammation and scarring, both important factors in chronic kidney disease getting worse (Agarwal et al. 2022; Filippatos et al. 2022). Both treatments have shown good results in separate tests, but we don't yet have enough information about how they compare to each other in people who have diabetes, high blood pressure, and obesity.This research will assess and contrast how well SGLT2 inhibitors and finerenone work at slowing down the worsening of chronic kidney disease in overweight, diabetic patients with high blood pressure. We're using a 'comparative effectiveness' approach, bringing together information from clinical trials, studies observing patients, and combined data. We'll be looking at how eGFR changes and how quickly the disease reaches advanced stages as the main results, and also at heart problems, hospital admissions, and any side effects from the treatment.New research suggests SGLT2 inhibitors are particularly good at reducing overactivity of the glomeruli and improving blood flow in the kidneys, while finerenone has extra benefits due to its ability to reduce inflammation and scarring. The FIDELITY analysis, for example, showed finerenone significantly lowered both kidney and heart-related problems in people with type 2 diabetes and chronic kidney disease (Agarwal et al. 2022). And SGLT2 inhibitors have regularly and considerably reduced the progression of kidney disease and the risk of heart failure in many different groups of people (Yau et al. 2022; Dabour et al. 2024).We expect this study's results to give an important understanding of how the two therapies work in relation to each other, and how they can complement one another, particularly in people with multiple, serious conditions. By clarifying which is better, this research is designed to help doctors make decisions about treatment and improve how we slow down chronic kidney disease. What's more, it points to the possibility of using the two drugs together; current trials like CONFIDENCE (Green et al. 1023) suggest this might be the next step forward in treating chronic kidney disease.In short, both SGLT2 inhibitors and finerenone are significant improvements in managing chronic kidney disease in patients with obesity, high blood pressure, and diabetes. However, because they work in different ways and have different effects, it's important to have treatments tailored to the individual. We need further trials where the drugs are tested against each other and longer-term studies to decide the best course of treatment and get the best possible results for patients.